Early management of neurologic clubfoot using Ponseti casting with minor posterior release in myelomeningocele: a preliminary report. Issue 2 (March 2016) - Abo El-Fadl, Sameh; Sallam, Asser; Abdelbadie, Ahmed
Abstract : This study aimed to examine the results of manipulation and serial casting, followed by open Achilles lengthening combined, when necessary, with posterior release in the management of neurologic clubfoot in infants with myelomeningocele. This study was carried out prospectively with a minimum follow-up of 2 years on 24 consecutive infants (48 feet) with neurologic insensate feet. Manipulation and serial casting were performed, followed by open tendo Achilles lengthening with/without posterior capsulotomy of the ankle and subtalar joints. The Diméglio scoring system was used to assess the degree of deformity correction immediately postoperatively and the latest follow-up visits. The mean age of the patients at initial treatment was 5.9 (3–8) weeks. None of the patients was lost to follow-up. For 36 feet, the final range of scores was 5–6 and the deformities were grade II of moderate type. Only for seven of 48 feet the final scores were in the range 10–12, grade III, and severe type. Only three infants (5/48 feet) failed to show any improvement. We thus support this treatment for the management of insensate feet of infants with myelomeningocele soon after birth as most infants responded satisfactorily in terms of deformity correction and achieved plantigrade mobile feet that fit into orthotics.